ӨСПИРИМЛЕР ҲӘМ БАЛАЛАРДЫҢ ҲӘР ТӘРЕПЛЕМЕ РАЎАЖЛАНЫЎЫНДА ДЕНЕ ТӘРБИЯСЫНЫҢ МАҚСЕТИ ҲӘМ ЎАЗЫЙПАЛАРЫ - Тойлибаев, С.М.; Кеңесбаева, Д.Б. (SCIENCE and SOCIETY, 2017)
In the article it is told about the purposes and problems of physical training for all-round development of children and teenagers. At the same time all necessary upbringing and educational components at occupations by physical training and sport have been distinguished.
Keywords: all-round development of children and teenagers; spiritual education; physical development; problems of physical training; development of force; development of speed; endurance development